Propuesta de factibilidad para la creación de un restaurante de comida tradicional, en el barrio Guitig Alto, cantón Mejía, provincia de Pichincha - Changoluisa Paneluisa, Adriana Lizbeth (2024)
The present research work seeks to propose the feasibility of the creation of a traditional food restaurant in the Güitig Alto neighborhood, seeing the need to have an infrastructure dedicated to food and beverage service, applying a descriptive approach of transversal axis in the research. In the bibliographic research, different sources were consulted, such as books, theses, PDOT, and websites of the Ministry of Tourism. This made it possible to identify the different phases of the project and to understand the parameters needed for each study. A field research was conducted using the survey technique using a 25-question questionnaire and a non-probabilistic convenience sampling type was used, which means that participants were selected based on their availability and accessibility allowing the market study to be established. To carry out the technical study, technical matrices were used to help analyze the external factors that could affect the project, and graphic design software called AutoCAD was used to determine the technical aspects of the project, such as the design and distribution of the spaces. In addition, an organizational chart was drawn up to present each of the departments that will be part of the restaurant. Finally, an analysis of the necessary investments, expected revenues, projected expenses, and financial statements was developed using tools such as Net Present Value, Internal Rate of Return, and Cost/Benefit analysis.